Philosophical Counseling or The Modern-Day Quest for Wisdom - Demircioglu, A. (NLC “Karaganda National Research University named after аcademician Ye.A. Buketov”, 2026)
Philosophical counseling, a form of philosophical practice, is an increasingly popular field that seeks to apply philosophical methods to address concrete problems, dilemmas, and search for meaning in daily human life. In its modern sense, philosophical counseling was initiated in Germany in 1981 by Archenbach. Transcending academic boundaries, philosophical practitioners aim to cultivate openness, wisdom, and a reflective life by interacting with individuals, groups, and organizations in a dialogical process. This article offers a comprehensive examination of the historical and conceptual origins of philosophical counseling, tracing them back to great ancient philosophical traditions, particularly the Socratic method. This study aims to reveal the fundamental principles, methods, and ethical frameworks that distinguish philosophical counseling from psychotherapy and life coaching. Furthermore, this work examines major models of practice and the critical issues facing the field of philosophical counseling, theoretical consistency, and its relationship with mental health. Additionally, it examines the challenges involved in applying philosophical counseling in organizational, educational, or social settings, as well as the potential future directions of philosophical counseling.
Философиялық кеңес беру немесе қазіргі заманғы даналықты іздеу
Философское консультирование или Современный поиск мудрости
Keywords: Philosophical counseling; philosophical practice; existential meaning; meaningmaking; Socratic dialogue; applied philosophy; ethical reflection; rational inquiry; eudaimonia; contemporary culture